PERANAN IDEOLOGI PANCASILA DI TENGAH ARUS GLOBALISASI DALAM KEHIDUPAN BERNEGARA - Fernanda, Naufal Rizky Fernanda (The Indonesian Journal of Social Studies, 2023)
This article discusses the crucial role of the Pancasila ideology in the life of the Indonesian state amid the rapidly evolving tide of globalization. Globalization has brought complex impacts on Indonesian society and politics, and the Pancasila ideology serves as a crucial guide in maintaining the stability and integrity of the nation. The article explains how Pancasila functions as a framework of values, a guide in international relations, and a foundation for just public policies in the context of globalization. The implications of Pancasila in government decision-making and the formation of national identity are also analyzed in this article, highlighting the relevance and significance of the Pancasila ideology in shaping life in the present era. In the current era of globalization, the values embedded in Pancasila are increasingly fading. This situation can be observed through the emergence of numerous problems due to the failure to practice the values inherent in Pancasila. If not addressed promptly, the values within Pancasila may fade away (Regiani & Dewi, 2021) Keywords: Ideology, Pancasila, Globalizationa